2010
DOI: 10.1213/ane.0b013e3181c84e4e
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Effectiveness Study of Loss of Resistance to Air or Saline for Identification of the Epidural Space

Abstract: When used at the anesthesiologist's discretion, there is no significant difference in block success between air and saline for localization of the epidural space by LOR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…We did not compare contrast with saline because Segal and Arendt have reported that the isotonic saline returning from a blocked needle might sometimes be mistaken for cerebrospinal fluid when the Tuohy needle is not yet in the epidural space, resulting in a failed block [ 3 ]. In the cervical region, anatomical studies have shown not only high rate of discontinuity, but also anatomic variability in the ligamentum flavum, which plays an inevitable role in the LOR technique.…”
Section: Discussionmentioning
confidence: 99%
“…We did not compare contrast with saline because Segal and Arendt have reported that the isotonic saline returning from a blocked needle might sometimes be mistaken for cerebrospinal fluid when the Tuohy needle is not yet in the epidural space, resulting in a failed block [ 3 ]. In the cervical region, anatomical studies have shown not only high rate of discontinuity, but also anatomic variability in the ligamentum flavum, which plays an inevitable role in the LOR technique.…”
Section: Discussionmentioning
confidence: 99%
“…With the LOR technique, a sudden change in resistance is detected by the easier injection of air, saline or both, and this is associated with the passage of the epidural needle tip from the ligamentum flavum into the epidural space [4-6]. …”
Section: Introductionmentioning
confidence: 99%
“…Though saline has not been proven superior to air,[676869] various anecdotal reports question safety of LOR to air. Injection of air into EDS has been associated with paresthesias, difficult catheter insertion, partial block, accidental dural puncture, and postdural puncture headache.…”
Section: Discussionmentioning
confidence: 99%